From Abandoned Land to Economic Hub: Assessing the Revitalization of Beran Field, Bangunsari Village, Indonesia - Fitriani, Hanik (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
The revitalization of the Beran Field in Bangunsari Village, Dolopo District, and Madiun Regency has transformed an abandoned area into a vibrant public space and tourist destination, significantly impacting the welfare and economy of the local community. This study analyzes the strategies implemented by the local government, the forms of revitalization undertaken, and the resulting effects on the community. The two-stage revitalization process involved physical interventions such as the construction of a jogging track, playground, and improved facilities. The establishment of the "Guyub Rukun Sejahtera’ traders' association played a crucial role in enhancing the economic well-being of local residents, many of whom relied on trade in the field for their livelihood. The revitalization has not only stimulated economic growth but has also fostered greater social interaction, making Beran Field a hub for community activities. The study employed a descriptive-analytic approach, utilizing qualitative methods, such as in-depth interviews, observations, and surveys, to gather data from traders, local officials, and residents. The findings suggest that revitalization has had a notable positive impact on the community's standard of living with increased income levels and improved social dynamics. This study serves as a valuable reference for policymakers and researchers interested in community-based public space development strategies to spur socioeconomic progress.